The Key Knowledge Workers in the Process of Sharing Knowledge: Motives and Conditions - Morawski, Mieczysław (Journal of Corporate Responsibility and Leadership, 2020)
Purpose: The purpose of the study is to identify motives and conditions acting as incentives for key knowledge workers to share their individual knowledge with other employees. Methodology: The interviews with key knowledge workers of 50 companies operating in Poland were employed as the main data collection method. In the process of analysis, the interview findings were compared with the results of the questionnaire survey conducted among entrepreneurs and managers representing the companies of the interviewed key knowledge workers. Findings: The motives of knowledge sharing by key knowledge workers are as follows: financial motivation, sense of responsibility for the results of the organization and the results of teamwork, building and consolidating professional authority. The following conditions are required to be established to support knowledge sharing by key knowledge workers: organic leadership, organization of team work, communication processes, HR processes. Practical implications: Achieving high results in knowledge sharing with the participation of key knowledge workers requires a comprehensive knowledge management system. The knowledge-oriented enterprises have to create the adequate working environment for the key knowledge workers. The comfort zone for such employees guarantees that they become aware investors of their own intellectual capital. Their engagement in the knowledge sharing process is the key issue in regard to achieving the long-term, sustainable competitive advantage. Originality/value: The originality of the study derives from the fact that the issue of motives and conditions for key knowledge workers to share their knowledge has not been much studied, especially in the context of the companies operating in Poland. Comparing and contrasting the opinions of the interviewed key knowledge workers with the point of view represented by the entrepreneurs and managers of their companies provides additional value. Paper type: Research paper.